Yoga for Managing Dysmenorrhea and Well-being in Women: A Literature Review Throughthe Lens of Tri Hita Karana - Veronica Aurelie Buntoro; dr. Aditya Prabawa, M.Biomed, Sp.OG; Jerroll Septian Tammubua; Made Ajiswara Laba; Ayu Putu Githa Maheswari; I Gusti Ayu Intan Pramesti Utami; Laras Nazillah Putri (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Introduction: Dysmenorrhea significantly impacts women’s quality of life andwell-being. Yoga is considered an effective non-pharmacological intervention.Dysmenorrhea significantly influences women’s quality of life and overall well-being. Yoga is considered as and effective non-pharmacological intervention formanaging dysmenorrhea. Primary dysmenorrhea can lead to considerablephysical discomfort and emotional distress, ultimately resulting in a decline inoverall quality of life. Implementing yoga practices may provide substantialbenefits in alleviating dysmenorrhea.Methods: A systematic literature review was undertaken using PubMed andGoogle Scholar, focusing on the years 2015-2025. The selected keywords for thisreview included 'yoga', 'dysmenorrhea', and 'quality of life'. The review specificallytargeted peer-reviewed studies in any language focusing on women with primarydysmenorrhea. Following the screening of titles and abstracts, relevant full-textarticles were analyzed to extract key findings.Discussion: To analyze scientific evidence regarding the role of yoga in themanagement of dysmenorrhea and its potential to enhance overall well-beingthrough the perspective of Tri Hita Karana philosophy. This approach encouragesa holistic understanding of health and wellness.Conclusion: Yoga plays a vital role in enhancing pain relief, fostering emotionalbalance, and creating a holistic connection that aligns with Tri Hita Karanaprinciples. Yoga and Tri Hita Karana can offer a sustainable approach topromoting women’s health and well-being.